2013
DOI: 10.3844/ajabssp.2013.199.203
|View full text |Cite
|
Sign up to set email alerts
|

HOST PATHOGEN INTERACTION STUDY IN MALFORMED AFFECTED TISSUES OF <i>MANGIFERA INDICA</i> L.

Abstract: The malformation disease of mango by Fusarium moniliforme var. subglutinan is one of the major causes of huge economical loss every year. Early diagnosis of the pathogens can help cultivators to protect the mango orchid and fruits from successive and secondary infection. The molecular detection is one of the better choices among available techniques for diagnosis. But the farmers or individual cultivars from tropical and subtropical countries like India, Pakistan, Malaysia, Vietnam, Philippines, have lots of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The gathering of stubby leaves into close folds similar to incipient bunchy top met under natural normal conditions, which is in accordance with previous workers [9,32] on pathogenicity. Early and easy disease detection of F. mangiferae is necessary for effective and timely management of mango malformation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The gathering of stubby leaves into close folds similar to incipient bunchy top met under natural normal conditions, which is in accordance with previous workers [9,32] on pathogenicity. Early and easy disease detection of F. mangiferae is necessary for effective and timely management of mango malformation.…”
Section: Discussionsupporting
confidence: 91%
“…subglutinans) isolated from floral and vegetative malformed tissues [8] as evidenced by cultural and morphological data. Histopathological studies of floral and vegetative tissues confirmed the association of F. mangiferae [9] . According to recent classification, F. subglutinans now registered as F. mangiferae causing mango malformation disease [6,[10][11][12][13] .…”
Section: Introductionmentioning
confidence: 60%
“…[3][4][5] The fungus is reported as a pathogen that affects leaves, inflorescences and fruits in pre and post harvest. In the postharvest phase, anthracnose is reported to cause losses of 5 to 20% 6 and the use of synthetic chemical fungicides and treatment with hot water at 52±2 °C for 10 min have been suggested to minimize damage to mango fruits. 7,8 As well as the use of natural and biodegradable biofungicides, such as trans-cinnamaldehyde, citral and phenylacetaldehyde, for the control of anthracnose disease in mango after harvest.…”
Section: Introductionmentioning
confidence: 99%
“…In general, higher levels of auxins were found in healthy panicles of mango as compared to malformed panicles, also in addition to the lower levels of lAA in affected tissues and enlarged. Accordingly, it has been suggested by Kumar et al (2013) that, the deformation may be due to the low level of auxins, which leads to hormonal imbalance. The use of chemicals as a foliar application has been shown to be effective in reducing mango deformation disease, as it may delay or advance the onset of flowering (Sanjay et al 2018).…”
Section: Introductionmentioning
confidence: 99%